(untitled) (Editora Impacto Científico, 2025)
This article addresses the importance of teacher professional development and inclusion policies in the care of children with Autism Spectrum Disorder (ASD) in early childhood education. Through a bibliographical survey, the challenges faced by teachers were analyzed, especially those related to insufficient initial training and the need for structured continuing training. The relevance of the link between theory and practice was highlighted, as well as the importance of psycho-pedagogical support and the partnership between school and family in building inclusive environments. The use of specific teaching resources, such as assistive technologies, games and alternative communication, is fundamental to promoting the engagement and learning of these students. It also emphasizes the affective dimension of teacher mediation, which contributes to the creation of bonds of trust and security. The article also shows that, despite the existence of legal frameworks that guarantee the right to inclusion, there are still significant challenges to its implementation in the school context. Finally, it highlights that the inclusion of children with ASD requires an integrated commitment, involving training, adequate resources, institutional support and welcoming attitudes, with a view to building an early childhood education that respects and values diversity.